Mytilus trossulus introgression and consequences for shell traits in longline cultivated mussels. (10th May 2021) - Michalek, Kati; Vendrami, David L. J.; Bekaert, Michaël; Green, David H.; Last, Kim S.; Telesca, Luca; Wilding, Thomas A.; Hoffman, Joseph I.
Abstract: Mussels belonging to the Mytilus species complex ( M . edulis, ME ; M . galloprovincialis, MG ; and M . trossulus, MT ) often occur in sympatry, facilitating introgressive hybridization. This may be further promoted by mussel aquaculture practices, with MT introgression often resulting in commercially unfavourable traits such as low meat yield and weak shells. To investigate the relationship between genotype and shell phenotype, genetic and morphological variability was quantified across depth (1 m to 7 m) along a cultivation rope at a mussel farm on the West coast of Scotland. A single nuclear marker (Me15/16) and a novel panel of 33 MT ‐diagnostic single nucleotide polymorphisms were used to evaluate stock structure and the extent of MT introgression across depth. Variation in shell strength, determined as the maximum compression force for shell puncture, and shell shape using geometric morphometric analysis were evaluated in relation to cultivation depth and the genetic profiles of the mussels. Overall, ME was the dominant genotype across depth, followed by ME × MG hybrids and smaller quantities of ME × MT hybrids and pure MT individuals. In parallel, we identified multiple individuals that were either predominantly homozygous or heterozygous for MT ‐diagnostic alleles, likely representing pure MT and first‐generation ME × MT hybrids, respectively. Both the proportion of individuals carrying MT alleles and MT allele frequency declined with depth. Furthermore, MT ‐introgressed individuals had significantly weaker and more elongate shells than nonintrogressed individuals. This study provides detailed insights into stock structure along a cultivation rope and suggests that practical methods to assess shell strength and shape of cultivated mussels may facilitate the rapid identification of MT, limiting the impact of this commercially damaging species.